Does Shyness Foster Online Connections? An Analysis of Its Role in Relationship Initiation - Aulianisa Radhiyya Paryanto; Andromeda (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Relationships developed online represent a new way for individuals to form personal connections with others. Shy individuals feel more comfortable interacting online because there is no direct evaluation when interacting with others. The purpose of this study is to examine the relationship between shyness and the initiation of online relationships. This study employed a quantitative research method with a cross-sectional design. The population in this study consists of young adults who use online media. The sample was selected using non-probability sampling, specifically convenience sampling (accidental sampling), comprising 100 participants. Analysis was conducted using simple and multiple linear regression. The results indicate that online relationship initiation does not have a significant effect on shyness (β = −0.128; p = 0.205). In the multiple regression model, only the romantic dimension had a significant effect and was negatively correlated with shyness (β = −0.429; p = 0.014), whereas friendship and sex were not significant. The coefficient of determination (R² = 0.072) indicates that the contribution of relational variables to shyness is relatively small. These findings suggest that romantic relationships in online relationships have the potential to serve as a protective factor against social inhibition. This study enriches the literature on the psychological dynamics of initiating online relationships by emphasizing the importance of relationship depth over the mere existence of social connections.